Structural anisotropy method for shells with orthogonal stiffeners. (December 2021) - Karpov, V.V.; Semenov, A.A.
Abstract: This paper proposes a smeared stiffener method: a structural anisotropy method used to analyze stiffened shell structures. It addresses the principle of the method, which involves reducing a structure of discretely variable thickness to a shell of uniform thickness with equivalent stiffness. Such an approach can take into account shear and torsional rigidity of stiffeners. The authors provide a literature review and present a geometrically nonlinear mathematical model. For analysis, the authors use an algorithm based on the Ritz method and the best parameter continuation method. They present results of calculations for stiffened shallow doubly curved shells, and for cylindrical and conical panels. The authors also demonstrate that the method converges as the number of stiffeners increases. Stiffener ribs of the considered structures gave an increase in the critical buckling load by 40–200 percent with a rib grid of 4 by 4, and an increase by 100–350 percent with a rib grid of 16 by 16. Such a scatter of values is due to significantly different input parameters of structures.